Nation Against Nature: From the Global Border to the Cross‐Border Commons. (2nd January 2020) - Cruz, Teddy; Forman, Fonna
Abstract: Teddy Cruz and Fonna Forman are professors at the University of California, San Diego. Here they discuss their practice investigations of the border conditions between Mexico and the US, proposing a Cross‐Border Commons of political coalitions, ecological zones and new forms of citizenship.